Analysis of Nursing Practice in NSTEMI Patients: The Effect of Autogenic Relaxation Combined with Nature Sound Music Therapy on Blood Pressure Stabilization in the ICCU - Ayu Nuriana; Zulmah Astuti; Ulfatul Muflihah; Dwi Widyastuti (International Journal of Public Health Excellence (IJPHE), 2026)
Non-ST Elevation Myocardial Infarction (NSTEMI) is often accompanied by increased blood pressure due to pain and anxiety, which trigger activation of sympathetic nervous system, thereby increasing cardiac workload and worsening myocardial ischemia. In addition to pharmacological therapy, non- pharmacological interventions are needed to help stabilize patients' hemodynamic status. This study aimed to analyze the implementation of autogenic relaxation combined with nature sound music therapy on blood pressure in patients with NSTEMI. A case study was conducted on one NSTEMI patient in the Intensive Cardiac Care Unit (ICCU), where blood pressure was measured before and after intervention. The findings showed that the patient who received autogenic relaxation combined with nature sound music therapy experienced a decrease in both systolic and diastolic blood pressure and a more relaxed condition. In conclusion, autogenic relaxation combined with nature sound music therapy is effective as a supportive non-pharmacological intervention in stabilizing blood pressure in patients with NSTEMI.